2020
DOI: 10.1007/s10237-020-01349-w
|View full text |Cite
|
Sign up to set email alerts
|

Collagen fibre orientation in human bridging veins

Abstract: Bridging veins (BV) drain the blood from the cerebral cortex into dural sinuses. BV have one end attached to the brain and the other to the superior sagittal sinus (SSS), which is attached to the skull. Relative movement between these two structures can cause BV to rupture producing acute subdural haematoma (ASDH), a head injury with a mortality rate between 30 and 90%. A clear understanding of the BV's microstructure is required to increase the biofidelity of BV models when simulating head impacts.Twelve fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Furthermore, quantification of BVs is more objective than quantification of cystic structures, given that cystic structures are challenging to identify due to difficulties in tracing cyst edges. BVs, by definition, connect the cortical veins to the SSS [15]. In addition, we use BVs ≥ 3 mm in diameter and cystic structures or AGs within 1 cm of the confluence as inclusion criteria for more objective quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quantification of BVs is more objective than quantification of cystic structures, given that cystic structures are challenging to identify due to difficulties in tracing cyst edges. BVs, by definition, connect the cortical veins to the SSS [15]. In addition, we use BVs ≥ 3 mm in diameter and cystic structures or AGs within 1 cm of the confluence as inclusion criteria for more objective quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Interessanterweise ordnen sich Kollagenfasern in der 3-dimensionalen Struktur der durch den Umbau veränderten Venenwand an. Diese Studie wurde jedoch durchgeführt, um Brückenvenen (BV) zu untersuchen, die das Blut aus der Hirnrinde in die Sinus der Dura-Mater ableiten, und hat die Bedeutung der Anordnung von Kollagenfasern dieser Venen nach einem Gewebeumbau aufgezeigt [9]. In Varizen kommt es bei den Kollagenfasern durch die veränderte räumliche Anordnung zu einer Lücke mit einem möglichen Zusammenhang mit Risikofaktoren.…”
Section: Extrazelluläre Matrix Der Venenwandunclassified
“…Interestingly, the collagen fibers have a natural disposition to the tridimensional structure of the vein walls that is altered due to tissue remodeling. Despite that, this study was conducted to study bridging veins (BVs), which drain the blood from the cerebral cortex into the Dural sinuses, demonstrating the importance of collagen fiber disposition on those veins after tissue remodeling head impact [9]. Thus, there is a gap in collagen fibersʼ spatial configuration changes in varicose veins and a potential link to risk factors.…”
Section: Extracellular Matrix Of the Vein Wallmentioning
confidence: 99%
“…Collagen fibres have also been shown to have a significant role in the intralamellar bonding of tissues [36]. Histological studies have revealed that the seemingly disordered distribution of collagen fibres in a tissue, can actually be shown to have a mean orientation which are not aligned along the main loading directions of a tissue [37], [38], [33], [39]. These studies on the orientation of collagen fibres clearly reveal a general oblique alignment of the fibres with respect to the direction of loading.…”
Section: Motivation For the Current Studymentioning
confidence: 99%